2011
DOI: 10.1063/1.3606418
|View full text |Cite
|
Sign up to set email alerts
|

Detection of charge density wave ground state in granular thin films of blue bronze K0.3MoO3 by femtosecond spectroscopy

Abstract: During the last years, femtosecond time-resolved spectroscopy (fsTRS) has become an important new tool to investigate low energy excitations in strongly correlated systems. By studying energy relaxation pathways linking various degrees of freedom (e.g., electrons, spin, or lattice), the interaction strengths between different subsystems can be deduced. Here we report on yet another application of fsTRS, where the technique is used to unambiguously determine the nature of the ground state in granular thin films… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…However, a smeared feature appeared in the logarithmic derivative of R(T) in respect to 1/T around 150 K, similarly as in highly doped BB samples and patterned BB wires [1]. At the same temperature, the Raman-active CDW amplitude mode appears in fs-TRS [3,5]. The films with lower resistance and a more pronounced anomaly at 150 K also had better texture, the grains preferably ordered in orthogonal directions, as observed by atomic force microscopy (AFM) [4,5].…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…However, a smeared feature appeared in the logarithmic derivative of R(T) in respect to 1/T around 150 K, similarly as in highly doped BB samples and patterned BB wires [1]. At the same temperature, the Raman-active CDW amplitude mode appears in fs-TRS [3,5]. The films with lower resistance and a more pronounced anomaly at 150 K also had better texture, the grains preferably ordered in orthogonal directions, as observed by atomic force microscopy (AFM) [4,5].…”
Section: Introductionmentioning
confidence: 77%
“…We have previously reported on the production of the BB thin films by pulsed laser deposition (PLD) [3]. Standard characterization techniques showed that our films are composed of nanocrystalline grains [3][4][5], while the presence of the CDW in grains below 150 K was unambiguously demonstrated by the observation of CDW amplitude mode in femto-second time resolved spectroscopy (fs-TRS) [3].…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations